Teacher-Student Translanguaging Interaction: A Discourse Analysis of Eliciting Responses in EFL Classrooms - Fadly Umadji; Hasanuddin Fatsah; Muziatun; Rasuna Talib; Rahman Taufiqrianto Dako (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study investigates the strategic utilization of translanguaging within teacher-student interactional sequences to elicit and facilitate student responses in the English as a Foreign Language (EFL) classroom of SMA Negeri 11 Gorontalo Utara. Set within the rural, multi-ethnic educational context of Gentuma Village, which is deeply characterized by the local sociocultural philosophy of Huyula (mutual cooperation), this research challenges traditional monolingual biases in language pedagogy. Employing a qualitative descriptive case study design oriented towards classroom discourse analysis. The analysis strictly integrates Doff’s (2012) taxonomy of elicitation techniques encompassing questioning, visual aids, games, texts, and non-verbal cues, with contemporary translanguaging pedagogical frameworks. The results demonstrate that the teacher systematically orchestrates a sophisticated "symphony of languages," fluidly mobilizing English, Indonesian, Gorontalo, Javanese, Sanger, and Manado Malay to activate students' background knowledge, lower the affective filter, and prompt active verbal participation. Specifically, visual and game-based elicitation techniques proved highly effective when coupled with translanguaging, transforming the rigid Initiation-Response-Feedback (IRF) sequence into a collaborative, hybrid interactional space. The findings reveal that translanguaging elicitation is not a remedial necessity for linguistic deficits, but a culturally sustaining pedagogical strategy that leverages local linguistic repertoires to build global communicative competence. This study provides empirical evidence that validating multi-ethnic identities within the EFL classroom fosters an inclusive learning environment, significantly enhancing students' willingness to communicate and overall classroom interactional competence